The Acute Effects of Varying Frequency and Pulse Width of Transcutaneous Auricular Vagus Nerve Stimulation on Heart Rate Variability in Healthy Adults: A Randomized Crossover Controlled Trial - Peter Atanackov; Jakob Peterlin; Maja Derlink; Uroš Kovačič; Nataša Kejžar; Fajko F. Bajrović (Biomedicines)
Background/Objective: Heart rate variability (HRV) is a key biomarker of autonomic function, linked to morbidity and mortality across various diseases. Transcutaneous auricular vagus nerve stimulation (taVNS) shows therapeutic promise, but its effects on HRV and the influence of specific stimulation parameters remain unclear. This study investigated whether the acute effects of taVNS on HRV depend on combinations of stimulation frequency and pulse width. Methods: Seventy-eight healthy adults participated in seven randomized sessions, each testing one of six active taVNS protocols or an inactive sham condition applied to the cymba conchae of the left ear. The active protocols varied by frequency (10 Hz or 25 Hz) and pulse width (100 µs, 250 µs, or 500 µs). The sessions included 15 min of baseline, 15 min of taVNS or sham condition, and 10 min of recovery. HRV was calculated using the standard deviation of NN intervals (SDNN) and the root mean square of successive differences (RMSSD) from continuous ECG recordings. Results: The 10 Hz/250 µs, 10 Hz/500 µs, and 25 Hz/100 µs protocols significantly increased SDNN time series compared to the sham condition. Exploratory analysis revealed SDNN increases during the second 5 min of stimulation with the 10 Hz/500 µs protocol and during the first 5 min of recovery with the 10 Hz/250 µs and 25 Hz/100 µs protocols. No significant changes in the RMSSD were found for any protocol. Conclusions: TaVNS is safe in healthy adults, and specific frequency and pulse width combinations can acutely enhance overall HRV, as reflected in SDNN, but do not affect vagally mediated HRV, as reflected by the RMSSD. Future studies should optimize taVNS parameters to maximize physiological and clinical outcomes.